IDENTIFIKASI PRIORITAS ATRIBUT-ATRIBUT DI BIDANG PENGAJARAN DALAM RANGKA PENINGKATAN KINERJA DOSEN UNIVERSITAS DIAN NUSWANTORO - Hertiana Ikasari; Ngatindriatun Ngatindriatun (MEDIA, 2012)
The purpose of this study is identifying the attributes that should be prioritized by lecturers ofÂ  Dian Nuswantoro University in the field of teaching in order to improve its performance. This study uses primary data and secondary data. Secondary data are fromÂ  the lecturers presence and student midterm grades obtained from the Central Information Systems (PSI) UDINUS in second semester of 2011/2012. Primary data obtained from questionnaires to students about student perceptions regarding lecturer performance attributes that want to be judged. Analysis tools used in this study is Fuzzy Quantification Theory I. The greatest attribute to be prioritized is response capability factors and clarity of lecturer in answering questions from the students. Lecturers need to master the material that is being taught, so if there are any questions from the students can give a satisfactory answer. Advice that can be given is in giving the tasks in the field of teaching, the academic authorities should pay attention to propriety Normal Workload Tri Dharma University, the academic authorities should consider giving the teaching assignments according to their competencies.